Analysis of imaging in pediatric bronchopulmonary foregut malformations with literature review: case reports - Ji, Shaohua; Zhang, Hong; Guan, Yan; Song, Chen; Han, Meirong (Frontiers in Pediatrics, 2024)
Background: Bronchopulmonary foregut malformation (BPFM) is an uncommon 2 condition, with few case reports documented in both national and international literature. This scarcity underscores the importance of utilizing effective imaging techniques to improve our understanding and diagnostic precision concerning this disorder.Case Description: In the first case report, a neonate, born at full term and aged 15 days, presented with symptoms including dyspnea, coughing, wheezing, cyanosis, and vomiting. Initial diagnostic evaluations, which included chest radiography and upper gastrointestinal tract radiography, led to an erroneous initial diagnosis of a left-sided diaphragmatic hernia, accompanied by a suspicion of infection. In the second case report, another neonate, also born at full term but aged 5 days, exhibited symptoms such as coughing, choking, and mild vomiting. Utilizing a combination of computed tomography (CT) scans (plain, enhanced, and reconstructed), chest X-ray, and upper gastrointestinal tract radiography, the diagnosis of BPFM was accurately determined.Comprehensive imaging examinations play a crucial role in reducing misdiagnosis and diagnostic oversights in cases of BPFM. Given its rarity, BPFM often manifests as a sequestered lung accompanied by gastrointestinal abnormalities.Hence, the integration of CT scans with gastrointestinal tract radiography can substantially improve diagnostic precision in such cases.